1998
DOI: 10.1136/sti.74.6.448
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of hepatitis B markers among Mexican female sex workers

Abstract: Objectives: To estimate the prevalence and associated risk factors of hepatitis B virus (HBV) serological markers in female sex workers (FSW) in Mexico City. Methods: The study population consisted of 1498 FSW who attended a detection centre for human immunodeficiency virus (HIV) in Mexico City, between January and October 1992. Study participants responded to a standardised questionnaire and provided a blood sample for serology of syphilis, HIV, and HBV. Results: A total of 0.2% (95% CI 0.1-0.3) of the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
2
10
2
3
Order By: Relevance
“…The prevalence that was found in San Juanito is higher for young women when compared with Mexican female sex workers, although after the age of 33 years, the prevalence is lower in this community. 1 Prevalence is also higher in the population of San Juanito than the one observed in pregnant women in Mexico City, 11 in pregnant Mexican American women in San Francisco, 12 and in Hispanic and non-Hispanic women seeking gynecological care. 13 It is also substantially higher in the children of San Juanito than in children of the same age group (5-17 years) living in the Texas-Mexico border (5.2% versus 1%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The prevalence that was found in San Juanito is higher for young women when compared with Mexican female sex workers, although after the age of 33 years, the prevalence is lower in this community. 1 Prevalence is also higher in the population of San Juanito than the one observed in pregnant women in Mexico City, 11 in pregnant Mexican American women in San Francisco, 12 and in Hispanic and non-Hispanic women seeking gynecological care. 13 It is also substantially higher in the children of San Juanito than in children of the same age group (5-17 years) living in the Texas-Mexico border (5.2% versus 1%).…”
Section: Discussionmentioning
confidence: 92%
“…It has been considered that Mexico has a low prevalence of hepatitis B, 1 although recent estimates have suggested that its prevalence may be similar to the one observed in Central and South America countries. 2 The National Health and Nutrition Examination Survey (NHANES III), conducted in the United States in 1988-1994, showed a higher prevalence of hepatitis B infection in Mexican Americans when compared with the non-Hispanic white population of that country, mainly in those citizens Ն 50 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors determined by univariate or multivariate analysis and associated to anti-HBc prevalence by odds ratio (OR) were reported in general population [35], pregnant women [61], healthcare workers [66], and female sex workers [73]. The main risk factors were (i) age at first sexual intercourse above 25 years in general population and in pregnant women, with a reported OR of 3.24 (95% CI, 1.44-7.28) and 5.1 (95% CI, 1.4-19.1), respectively; and (ii) age above 33 years in female sex workers with an OR of 5.4 (2.2-13.0).…”
Section: Main Risk Factors For Hbv Infection In Mexican Populationmentioning
confidence: 99%
“…[7] c Ref. [35] workers [62][63][64][65][66][67], females sex workers [68][69][70][71][72][73][74][75], patients with liver diseases [29,40,76,77], hemodialysis patients [78,79], emergency department attendees [80], and psychiatric patients [81] are depicted in Table 2. The estimates from the native Mexican population [82][83][84] are also included in this group based on an HBsAg seroprevalence higher than the general population and blood donors.…”
Section: High-risk Groupsmentioning
confidence: 99%
“…Por lo tanto, el dato de la aparentemente elevada prevalencia del AgsHB entre las mujeres del estudio referido debe ser tomado con reserva. La prevalencia de ese marcador en poblaciones mexicanas de mucho mayor riesgo para hepatitis B como son trabajadoras del sexo comercial, 5,6 y hombres que tienen sexo con hombres, 7 se ha encontrado de manera global entre 0.2 y 1.9%, confirmando los positivo por neutralización.…”
Section: Consideraciones Técnicas Y Conceptuales Acerca De La Seropreunclassified